Próba optymalizacji rozdysponowania środków finansowych na rozwój obszarów wiejskich w Polsce z uwzględnieniem preferencji rolników woj. wielkopolskiego - Poczta, Walenty; Kiryluk, Ewa (Attempts of Operational Research of Financial Means Allocation on the Development of Country Regions in Poland with Taking Preferences of Farmers from Wielkopolska Voivodship into Consideration, 2005)
The increasing importance of rural development expenses rises new challenges to decision-makers. The aim of the paper is to optimize the rural development budget allocation in Poland, using linear programming approach. Farmers from Wielkopolska were asked for their opinion on measures importance. The computer-aided programming may be used as a tool in budget allocation decisions making.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 216-223